2017
DOI: 10.3390/ijerph14050483
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dog-Assisted Intervention on Student Well-Being, Mood, and Anxiety

Abstract: This novel, exploratory study investigated the effect of a short, 20 min, dog-assisted intervention on student well-being, mood, and anxiety. One hundred and thirty-two university students were allocated to either an experimental condition or one of two control conditions. Each participant completed the Warwick–Edinburgh Mental Well-Being Scale (WEMBS), the State Trait Anxiety Scale (STAI), and the UWIST Mood Adjective Checklist (UMACL) both before, and after, the intervention. The participants in the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 19 publications
9
98
0
1
Order By: Relevance
“…Our results are in line with previous research showing short-term psychological benefits of therapy dog sessions (Binfet, 2017;Crossman et al, 2015;Crump & Derting, 2015;Grajfoner et al, 2017;Katcher & Beck, 2010;McDonald, McDonald, & Roberts, 2017). However, unlike much previous research on this topic (e.g., Binfet & Passmore, 2016), our study was designed to mirror the conditions of a typical single drop-in group therapy dog session (e.g., Logan, 2016;Rollit, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are in line with previous research showing short-term psychological benefits of therapy dog sessions (Binfet, 2017;Crossman et al, 2015;Crump & Derting, 2015;Grajfoner et al, 2017;Katcher & Beck, 2010;McDonald, McDonald, & Roberts, 2017). However, unlike much previous research on this topic (e.g., Binfet & Passmore, 2016), our study was designed to mirror the conditions of a typical single drop-in group therapy dog session (e.g., Logan, 2016;Rollit, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…However, unlike much previous research on this topic (e.g., Binfet & Passmore, 2016), our study was designed to mirror the conditions of a typical single drop-in group therapy dog session (e.g., Logan, 2016;Rollit, 2016). Our study also fills a research gap regarding the longevity of therapy dog session benefits, as it examines effects at a time point between the immediate effects of a single drop-in therapy dog session (Grajfoner et al, 2017), the lack of effects 2 weeks later (J. Binfet, 2017), and the qualitative perceived effects 3 months later (Dell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, there is evidence that having a dog can reduce risk of depression; a recent survey of people living with HIV found that non-dog guardians had 3 times higher odds of depression compared to current dog guardians [22]. There is also evidence that companion dogs can reduce anxiety in children with autism spectrum disorder [23], and interaction with a dog has been found to reduce anxiety and increase wellbeing and positive mood in University students [24]. …”
Section: How Do Dogs Benefit Humans?mentioning
confidence: 99%